Hospitality revenue management : concepts and practices - Szende, Peter (Palm Bay, FL : Apple Academic Press, 2020)
"This new textbook, Hospitality Revenue Management: Concepts and Practices, provides a comprehensive, in-depth introduction to the basic concepts and best practices of hospitality revenue management. With a real-world, hands-on approach, the book places students in the role of a revenue manager striving to succeed in an ever-changing hospitality business environment. The book takes a unique multi-author, collaborative approach, with chapters from outstanding industry leaders who share their experience and provide the information necessary to arm students with the most up-to-date tools and methods they to be effective in the hospitality revenue management field. The chapters cover the important topics in hospitality revenue management, including hotel pricing, hotel segmentation, distribution channels, competitive analysis, hotel forecasting, performance analysis, market data, supply and demand management, and more. This comprehensive and contemporary textbook effectively meets the curricular requirements of undergraduate and graduate courses. The book can also be used as a reference for practitioners and as a text for executive education programs. Each chapter includes features to keep students interested and engaged. These include case studies, internet activities, team projects, spreadsheet assignments, brief histories, and more"--
Includes bibliographical references and index.
Keywords: Hospitality industry -- Finance; Hospitality industry -- Management; Revenue management